Pathotypes and Simple Sequence Repeat (SSR)-Based Genetic Diversity of Phytophthora sojae Isolates in the Republic of Korea - Ngoc Ha Luong; In-Jeong Kang; Hee Jin You; Sungwoo Lee (Microorganisms)
Phytophthora sojae is the causal agent of the Phytophthora root and stem rot in soybean, which has resulted in a significant increase in the incidence of the disease and substantial yield losses on a global scale. The proliferation of Phytophthora sojae can be mitigated through the development of Phytophthora-resistant soybean cultivars. A fundamental understanding of the genetic diversity and dynamic changes within the P. sojae population is essential for disease management and the development of new P. sojae-resistant varieties. Although a large number of pathogen samples can lead to more comprehensive interpretations and better conclusions, only six indigenous P. sojae isolates were available in the Republic of Korea at the time of the experiments. Due to the limited availability, this study preliminarily aimed to assess the pathotypes and genetic variation of the six P. sojae isolates collected in the Republic of Korea. The virulence patterns of all the six P. sojae isolates differed based on the 15 soybean differentials known for P. sojae resistance. The six isolates displayed high levels of pathotype complexities, ranging from 8 to 15, which is notably higher than those observed in other countries. Furthermore, 18 of the 21 simple sequence repeat markers used exhibited polymorphisms. The mean allele number (3.8) shows higher genetic variability compared to that (2.5) of isolates from the USA. The gene diversity (0.624) and the mean polymorphic information content (0.579) also displayed high levels of variation among the six isolates. A low mean heterozygosity (0.019) indicated a rare but possible outcrossing between the isolates, which was detected by the SSR marker PS07. Genetic dissimilarity assessments were employed to categorize the six P. sojae isolates into three groups using a neighbor-joining phylogenetic tree and principal component analysis. Although on a small scale, the phenotypic and genotypic assay results obtained indicated a significant variability in the pathotypes and genetic variation within the P. sojae isolates in the Republic of Korea. Though limited in scope, these results will be a cornerstone for elucidating the virulence pathotype and genetic diversity of the P. sojae population in future analyses. These findings also have the potential to improve the soybean breeding strategies aimed at enhancing resistance to P. sojae in the Republic of Korea.